Consumptive Behavior of Students on Free Shipping Promo at Shopee - Pita Marlenza; Sri Narti; Sapta Sari (Jurnal STIA Bengkulu, 2023)
This research is caused by the presence of consumer behavior that is much found among students.Students are the successors of a nation who are still experiencing a crisis of identity. where students perform consumer behavior in order to create their lifestyle.This consumer behavior is found in a lot among students.Where students perform consumer behavior in order to create their lifestyle.Purchase behavior originally serves to meet primary and secondary needs.Consumption is now growing at the same level as the quantity and variation of products becomes a consumer culture.The purpose of this research is to learn the student's consumer behavior on free promotions on shopee.Free promo is a free shipping fee.As we know together, generally sellers will pay a lot of costs for delivery of their products to buyers.This research is designed as a descriptive qualitative research. The events in the subject studied were described with a series of deep words or sentences, Structured, And logical based on the subject of study.